Integrasi Pengelolaan Limbah Kotoran Hewan Sapi dan Promosi Penyuluhan Kesehatan Upaya Mewujudkan Masyarakat Kelurahan Cipari Sejahtera - Zulfaidah, Rena; Khaerunnisa, Qalby; Sanjaya, Ramadhan Adi; Sururie, Ramdani Wahyu (Interdisciplinary Explorations in Research Journal, 2026)
This study aims to evaluate the impact of integrating livestock manure management and health promotion on community well-being, utilizing the SISDAMAS (Community Empowerment System) approach. Through a holistic perspective, this research analyzes how effective waste management can enhance environmental quality, public health, and provide economic benefits to farmers and surrounding communities. The findings are expected to yield comprehensive policy recommendations for achieving sustainable waste management and improving the quality of life. Additionally, this study will explore how health education can raise public awareness about the importance of maintaining environmental cleanliness and utilizing resources sustainably. Keywords: Management, Cow manure, Health education, SISDAMAS (Community Empowerment System)